An Analysis Of Students’ Problems In Writing Essays - Rahmi, Wahyuni; Sada, Clarry; Riyanti, Dwi (Syntax Corporation, 2024)
This research aimed to describe the problems sixth-semester English students face in writing essays and determine the factors that cause the problems. This research was designed to be qualitative, with a descriptive study as the methodology. The subject of this researcher was the twenty students in the sixth semester of the English language education study program, faculty of teacher training and education, Universitas Tanjungpura in the academic year 2022/2023, taken as the sample of the research by using the purposive sampling. Document analysis, qualitative surveys, and interviews were used to get the data. Tools of data collection used were documents, open-ended questionnaires, and interviews. The findings revealed that students had problems writing essays, especially with organization, mechanics, grammar, and vocabulary. Besides, it was also found that the factors caused the problems in writing essays were lack of knowledge, loss of motivation and practice,